Puškin Today - Bethea, David M. (Indiana University Press, 1993)
Puškin Today highlights the remarkable variety and compass of a figure who by all accounts is absolutely central to Russian culture, even "Russianness" itself. A multifaceted writer whose experiments at the boundaries of genre have never been equaled, Alexander Puškin is, moreover, an ever-evolving cultural myth; his works have served as a safe haven in troubled times for the Russian intelligentsia for nearly two centuries.